Exploring the Application of 5-axis CNC Machining for the Fabrication of an Impeller for Single Suction Centrifugal Pump - Samuel Bassey (International Journal of Manufacturing and Production Engineering, 2024)
This study delves into the practical application of 5-axis machining for the fabrication of an impeller for a single suction centrifugal pump. It explores the integration of CNC machining and CAD as a crucial aspect, highlighting the synergy between design and manufacturing. The efficiency and performance of the pump are greatly influenced by the impeller, an important part of pump design. Impellers made using traditional manufacturing techniques frequently have intricate designs and complicated geometries that are difficult to precisely manufacture. Using 5-axis CNC machining and other advanced manufacturing technologies presents a viable way to overcome these obstacles. By focusing on applications and the intricate interplay between machining and CAD, this research contributes to the advancement of 5-axis machining technology for precise and efficient complex component manufacturing
Keywords: 5-axis machining; CAD integration; CNC machining; Impeller; axis definition; complex components; machine-tool axes; manufacturing efficiency; production process